Survival analysis and determinants of timing of first birth after marriage in Nigeria (2016)
This study assessed the dynamics of First Birth Interval (FBI) after marriage, its determinants as well as relationship between fertility and FBI among women of reproductive age in Nigeria. We right-censored FBI of women aged 15-49 years using 201 3 Nigeria DHS data, used Kaplan Meier survival function to monitor the timings and Cox Proportional Hazard (CPH) and Generalized Gamma (GG) regression to model factors affecting FBI. The median FBI in Nigeria was 1.75 years and decreased with delayed age at marriage. Women with higher education have shorter FBI (TR=0.86(95% Cl: 0.85-0.88)). Urban women were more likely to have earlier FBI (HR= 1.28 95% C l: 1.24-1.32)). Fertility was significantly associated with FBI. The longer the FBI the lower the fertility level and vice versa except for women aged 15-19 years. Age at marriage, educational attainment, wealth status and residence were the main determinants of timing of first birth after marriage in Nigeria.